Baltic Sea during the Cold War: Polish-Soviet Maritime Cooperation - Będźmirowski, Jerzy; Gac, Miłosz; Kufel, Jakub (Historia i Polityka, 2024)
The end of hostilities on the European continent brought a hot war to a close but started the Cold War. Differences in the approach to many political and military issues of the future world created a divide among the allies. Each of them wanted to play a dominant role in the new reality. The possession of dreadful new weapons, nuclear weapons, singled out two of the most important “players” in the new world – namely, the United States of America and the Soviet Union. They were quickly identified as “superpowers”. The European continent, battered by World War II, was divided into two almost equal parts (arrangements in Tehran between Great Britain and the USSR, confirmed in Yalta), with the border running through the German territory. The dynamics of political changes in Europe led to the formation of the so-called Treaty of Dunkirk. At that time the Baltic Sea was the lens in which political and military events on the European continent focused. When the temperature in the East-West relations was rising, conceptual work began on the use of NATO and Warsaw Pact naval forces in the Baltic Sea. That work was subsequently verified during exercises that both sides conducted in this water region. The Baltic Straits were the proverbial “apple of one’s eye” – controlled by NATO naval forces but craved for by the naval forces of the United Baltic Fleet, seeking to take them over. And that was the most important problem of the Cold War: what to do and how to move the naval forces of the United Baltic Fleet to the North Sea. NATO, on the other hand, contemplated what to do and how to prevent that undertaking from happening. The Warsaw Pact’s concepts included the conquest of the Baltic Straits, occupation of the Jutland Peninsula, and launch of sea and land operations in the west direction. It was also assumed that NATO naval forces could carry out operations from the sea to the coast of the Polish People’s Republic and to that of the German Democratic Republic. Therefore, those variants were analyzed and exercised within the United Baltic Fleet and under the so-called combined forces (land and air). This article has been prepared based on Polish and foreign literature as well as archival materials from the Archives of the Institute of National Remembrance in Gdańsk, the Archives of New Records in Warsaw, and the Naval Archives in Gdynia.